The influence of microwave pulse conditions on enantiomer-specific state transfer - JuHyeon Lee; Johannes Bischoff; A O Hernandez-Castillo; Elahe Abdiha; Boris G Sartakov; Gerard Meijer; Sandra Eibenberger-Arias (New Journal of Physics, 2024)
We report a combined experimental and theoretical study on the influence of microwave pulse durations on enantiomer-specific state transfer. Two triads of rotational states within a chiral molecule (1-indanol) are selected to address the possible scenarios. In the triad connected to the absolute ground state, the simplest triad that exists for all chiral molecules, the enantiomer-specific state transfer process simplifies into a sequence of two-level transitions. The second triad, including higher rotational states, represents a more generic scenario that involves multiple Rabi frequencies for each transition. Our study reveals that the conventional $\frac{π}{2}-π-\frac{π}{2}$ pulse sequence is not the optimal choice, except for the ideal case when in the simplest triad only the lowest state is initially populated. We find that employing a shorter duration for the first and last pulse of the sequence leads to significantly higher state-specific enantiomeric enrichment, albeit at the expense of overall population in the target state. Our experimental results are in very good agreement with theory, substantiating the quantitative understanding of enantiomer-specific state transfer.